11 years of struggle, now Dr. Abdullah Fairuzullah has his PhD - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PAYA BESAR, 5 November 2022 - Armed with prayer, perseverance and patience, Dr. Haji Abdullah Fairuzullah Ahmad Tajuddin from the Centre for Information and Communication Technology (PTMK) successfully obtained a doctoral degree (PhD) in Computer Science after fighting for 11 years to finish his study.